2008
DOI: 10.1111/j.1365-294x.2008.03696.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptomics of life‐history trade‐offs in whitefish species pairs (Coregonussp.)

Abstract: Despite the progress achieved in elucidating the ecological mechanisms of adaptive radiation, there has been little focus on documenting the extent of adaptive differentiation in physiological functions during this process. Moreover, a thorough understanding of the genomic basis underlying phenotypic adaptive divergence is still in its infancy. One important evolutionary process for which causal genetic mechanisms are largely unknown pertains to life-history trade-offs. We analysed patterns of gene transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
178
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(197 citation statements)
references
References 88 publications
19
178
0
Order By: Relevance
“…The most represented functions were protein synthesis, cell growth, energy metabolism and muscle contraction. Transcripts involved in protein synthesis and cell growth exhibited systematically opposed additive effects to those associated with energy metabolism and muscle contraction , which is consistent with the observed trade-off in life-history traits and differential gene expression distinguishing dwarf and normal whitefish (St-Cyr et al 2008). Directional predominance of additive effects provides strong evidence for the role of directional selection in shaping genome architecture (Orr 1998).…”
Section: Elucidating the Genetic Bases Of Phenotypessupporting
confidence: 57%
See 1 more Smart Citation
“…The most represented functions were protein synthesis, cell growth, energy metabolism and muscle contraction. Transcripts involved in protein synthesis and cell growth exhibited systematically opposed additive effects to those associated with energy metabolism and muscle contraction , which is consistent with the observed trade-off in life-history traits and differential gene expression distinguishing dwarf and normal whitefish (St-Cyr et al 2008). Directional predominance of additive effects provides strong evidence for the role of directional selection in shaping genome architecture (Orr 1998).…”
Section: Elucidating the Genetic Bases Of Phenotypessupporting
confidence: 57%
“…It is also noteworthy that parallelism in patterns of gene expression was observed for the majority of those genes in microarray studies St-Cyr et al 2008) and that several loci linked to Lg3 had previously been found to be significantly resistant to introgression between whitefish from distinct glacial races (Rogers et al 2001). …”
Section: Mechanisms Of Reproductive Isolation and Their Genetic Basismentioning
confidence: 99%
“…Microarrays and, more recently, RNA-seq by means of NGS technologies have been used to compare the transcriptomes of phenotypically distinct individuals, namely in salmonid fishes St-Cyr et al, 2008;Goetz et al, 2010;Jeukens et al, 2010;Xu et al, 2010). Typically, many transcriptomic differences involved genes with functions related to energy production, muscular activity, immunity and cell cycle regulation processes.…”
Section: Gene Expression Among Crossesmentioning
confidence: 99%
“…Numerous studies have characterized genomewide patterns of gene expression among populations exhibiting phenotypic variation. In fishes in particular, the majority of such studies have not only used microarrays (Oleksiak et al, 2002;Whitehead and Crawford, 2005;Whitehead and Crawford, 2006;St-Cyr et al, 2008;Whiteley et al, 2008), but also next-generation sequencing to a lower extent (Elmer et al, 2010;Goetz et al, 2010;Jeukens et al, 2010;Shen et al, 2012). Hybridization can also lead to different modes of transcription regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still much to be learned about how divergent populations adapt to different environments under the effect of natural selection, which ultimately may evolve into biological species [3]. The new "omics" technologies, despite being very young, can contribute to this since they have taken up a very important position in the biological scientific landscape during the last decade [4].…”
Section: Introductionmentioning
confidence: 99%